Spigelian hernia after laparoscopic hysterectomy: Case report - Ozturk İnal, Zeynep and Inal, Hasan Ali and Alkan, Ender (Journal of Surgery and Medicine, 2018)
A Spigelian hernia, which may be congenital or acquired, is a rarely seen (0.12–2%) defect of the anterior wall of the abdomen, often causing pain or swelling. Surgical treatment is recommended because of complications such as ileus and strangulation. In this presentation, a case of Spigelian hernia in a 57-year-oldwomen who presented with abdominal pain and ileus and was diagnosed using a computerized tomography scan in the trocar entry is discussed in light of the literature.